Case of cholangiocellular carcinoma in a patient with glycogen storage disease type Ia. Issue 4 (18th July 2014) - Kanamori, Hiroyuki; Nakade, Yukiomi; Yamamoto, Takaya; Kobayashi, Yuji; Sato, Ken; Ito, Kiyoaki; Ohashi, Tomohiko; Nakao, Noiku; Ishii, Norimitsu; Takahashi, Emiko; Yokoi, Toyoharu; Nakao, Haruhisa; et al.
<x xml:space="preserve">Abstract</x> Glycogen storage disease (GSD) type Ia is caused by a deficiency in glucose‐6‐phosphatase. Long‐term complications, including renal disease, gout, osteoporosis and pulmonary hypertension, develop in patients with GSD type Ia. In the second or third decade, 22–75% of GSD type Ia patients develop hepatocellular adenoma (HCA). In some of these patients, the HCA evolves into hepatocellular carcinoma. However, little is known about GSD type Ia patients with HCA who develop cholangiocellular carcinoma (CCC). Here, we report for the first time, a patient with GSD type Ia with HCA, in whom intrahepatic CCC was developed.